(untitled) (ModaPalavra e-periódico, 2017)
Ergonomics aims to adapt products, services and strategies to make them compatible with the needs, abilities and limitations of people. Assistive technologies (AT) are devices, services, strategies and practices that reduce problems caused by functional limitations of individuals. They can help elderly to accomplish activities of daily living like dressing. Considering the aging of world population, this paper presents a research on interaction between the elderly and an assistive dressing aid to verify their perceptions about the use of the AT device. Five participants used the AT device to put a pair of socks, and evaluated this experience. We found that the main difficulty for elderly in using the device was understanding the manual. Participants could not dress the pair of socks completely. Completing the tests, we evaluated the instruments and highlighted the participant’s opinions regarding advantages and disadvantages of the product.